Compression constitutive relationship of RPC with different steel fiber content. (November 2020) - Yu, Xinmin; Fu, Benzhao; Chen, Shichuan
Abstract: Uniaxial compression tests were carried out on RPC with different steel fiber contents. The mechanical properties of RPC and the compressive-stress-strain curves of RPC with different steel fiber contents were studied. The results show that under the same mixture proportions, compressive strength increase with the increase of steel fiber content. When the steel fiber content is 3.5%, the compressive strength of RPC cubes is the largest; under the same mixture proportions, the compressive strength of RPC cube is approximately linear with the compression strength of prism, and the peak compressive strain and elastic modulus ratio of RPC cubes increase with the increase of steel fiber content. In this paper, the equation of the rising and descending sections of the stress-strain curves of different steel fiber volume admixtures is derived. According to the results of this test, the relationship between rising section, descending section coefficient and steel fiber content is obtained.)